Application of Digital Marketing Implementation of Perusahaan Listrik Negara (PLN) Mobile to Improve Customer Service at the Bukittinggi Customer Service Unit - Iman Rohmatan; Slamet Widodo (Yayasan Sinergi Kawula Muda, 2024)
Digital marketing has revolutionised customer service strategies in various industries including in Perusahaan Listrik Negara (PLN), currently PLN is facing a significant transformation towards the digital era, which affects various aspects of operations and services. These changes include the adoption of information and communication technology to improve efficiency in electricity distribution, customer data management, and service delivery. In this digital era, PLN strives to integrate technology solutions to improve the reliability of electricity supply, optimise network management, and provide more responsive services to customers. This can illustrate how PLN's efforts adjust to the challenges and opportunities that exist in the change towards the digital era, in this case PLN has presented a Mobile application in the form of PLN Mobile which aims to personalise interactions with customers, simplify service processes, and increase overall customer satisfaction. This abstract examines the extent to which digital marketing can optimise service and operational efficiency in the context of customer service improvement initiatives at ULP Bukittinggi.